SEMANTIC LOSSES AND SEMANTIC GAINS IN THE TRANSLATION OF REALIA - Khasanova Dildora Shukhratovna (International Journal of Literature and Language Studies, 2026)
This article examines the phenomenon of semantic losses and semantic gains in the translation of realia—culture-specific words and expressions that denote objects, phenomena, or concepts characteristic of a particular nation. The study analyzes how the transfer of linguocultural realia across linguistic boundaries inevitably involves both loss of source-culture meaning and acquisition of target-culture meaning, creating a dynamic of semantic transformation that complicates traditional equivalence-based approaches to translation. Drawing on translation theory, cultural linguistics, and comparative analysis of Uzbek-English and English-Uzbek translation examples, the research demonstrates that semantic losses and gains operate across multiple dimensions including denotative, connotative, associative, and pragmatic levels. The article argues that the translator's task is not to eliminate semantic losses—which is theoretically impossible—but to strategically manage the balance between losses and gains in accordance with the translation's communicative purpose and the target audience's interpretive needs.